Population genetics of Pseudobarbus phlegethon, Barbus calidus and Barbus erubescens (Teleostei: Cyprinidae) of the Olifants River System, Western Cape Province - Swartz, Ernst Roelof (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2000.